Early outcomes of hybrid coronary revascularization in multivessel coronary artery disease with low ejection fraction - Guz, Göksel; Avşar, Mustafa Kemal; Kırat, Barış; Önsel, İbrahim Özgür; Yorgancılar, Deniz; Ateşeal, Sabahattin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHybrid coronary revascularization (HCR), combining left internal mammary artery (LIMA) grafting to the left anterior descending artery (LAD) with percutaneous coronary intervention (PCI) for non-LAD lesions, has emerged as a potential strategy in patients with multivessel coronary artery disease (CAD) and severely reduced left ventricular ejection fraction (EF). However, data regarding its outcomes in this high-risk group remain limited.ObjectivesTo evaluate the early-term safety, feasibility, and clinical outcomes of HCR in patients with multivessel CAD and left ventricular dysfunction (EF 20%–35%).MethodsThis retrospective, single-center study included 50 consecutive patients with multivessel CAD and EF between 20% and 35% who underwent HCR between January 2022 and December 2024. HCR was performed with PCI for non-LAD lesions, followed by off-pump LIMA-to-LAD grafting. The primary endpoints were 30-day all-cause mortality and major adverse cardiac events (MACE). Secondary endpoints included hospital length of stay, perioperative complications, and 12-month outcomes.ResultsThe mean patient age was 65.4 ± 8.2 years, with 58% being male. Technical success was achieved in 96% of cases. The 30-day mortality rate was 2%, and the 30-day MACE rate was 8%, including myocardial infarction (4%), repeat revascularization (2%), and ischemic stroke (2%). New-onset atrial fibrillation occurred in 18% of patients, transient renal dysfunction in 10%, and prolonged ventilation (>24 h) in 4%. The mean hospital stay was 7.3 ± 2.1 days. At 12 months, the MACE-free survival rate was 88%, with a LIMA-LAD graft patency of 100% and saphenous vein graft patency of 92%. There was a modest improvement in EF from 28.6 ± 4.1% to 30.1 ± 4.5% (p = 0.12). Follow-up coronary angiography was performed in 48 patients (96%) at one year.ConclusionsHCR appears to be a feasible and relatively safe revascularization strategy for patients with multivessel CAD and severely reduced EF, offering acceptable early mortality and MACE rates. The excellent graft patency and low perioperative complication rates suggest that HCR may be a valuable alternative in this high-risk population, although larger multicenter trials are needed to confirm these findings.